Peacebuilding: the Shift towards a Hybrid Peace Approach - Syaiful Anam (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Unair, 2015)
This paper examines the transformation within the practice and concept ofcontemporary peacebuilding. Peacebuilding, practically and conceptually, hasbeen dominated by the liberal peace paradigm. In this case, theinstitutionalising of its core ideas such as democratisation, human rights, therule of law, and liberal market system to the post-conflict states and to a socalled ‘fragile/failed states’ aiming at bringing peace and security has failed to create a comprehensive and sustainable peace on the ground as exemplified in Nicaragua, Haiti, Bosnia, Afghanistan, and other post-war states. Scholars focused on the issue of peacebuilding have engaged to a new approach that challenge the domination of the liberal paradigm through the accommodation and appreciation upon the ‘local’ and thus create spaces for the interaction between the liberal and the ‘local’ within forms of ‘hybrid peace’ or ‘hybrid peacebuilding’